Distribution of polycyclic aromatic hydrocarbons (PAHs) in surface sediments of Langkawi Island, Malaysia - Chiu, Terence Ricky; Md Firoz Khan,; Mohd Talib Latif,; Mohd Shahrul Mohd Nadzir,; Haris Hafizal Abdul Hamid,; Hafidz Yusoff,; Masni Mohd Ali, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The individual compounds and sources of polycyclic aromatic hydrocarbon (PAHs) were studied in the surface sediments at 32 locations in the tourism area of Langkawi Island. A total of 15 PAHs were determined and quantified by gas chromatography coupled with mass spectrometry (GC-MS). The total PAH concentrations of surface sediments from Langkawi Island ranged from 228.13 to 990.25 ng/g and they were classified as being in the low to moderate pollution range. All sampling stations were dominated by high molecular weight PAHs with 4 rings (31.59%) and 5-6 rings (42.73%). The diagnostic ratio results showed that in most cases, the sampling stations have pyrogenic input. Further analysis using principal component analysis (PCA) combined with absolute principal component score (APCS) and multiple linear regression (MLR) showed that the natural gas emissions contributed to 57% of the total PAH concentration, 22% from the incomplete combustion and pyrolysis of fuel, 15% from pyrogenic and petrogenic sources and 6% from an undefined source.